3D Current Collectors for Lithium‐Ion Batteries: A Topical Review. Issue 8 (10th June 2018) - Yue, Yuan; Liang, Hong
Abstract: Current collectors play important roles in enhancing the electrochemical performance of lithium‐ion batteries. Currently used collectors are mostly made of aluminum or copper foils through slurry casting with binders that have not reached optimal capacity. Furthermore, extended cycles of charge and discharge induce detachment of the cast layer, resulting in damage to the structural integrity. In order to better understand the principles of the performance of and thus optimize current collectors, a critical review is conducted focusing on their structures. Through analysis of data collected from more than 50 publications, the capacity and retention as a function of current density and charge cycle, respectively, are identified. Two new terms, which are characteristic of 3D current collectors, are defined as Regime I and Regime II in the corresponding plots. Regime I refers to the maximum reversible capacity and Regime II to the maximum capacitor retention. The greater the values of those values, the greater the enhancement of capacity and retention. Using these concepts, it is predicted that carbonaceous and fibrous 3D hierarchical current collectors would be beneficial as battery collectors. The results and approach provide perspective for future design and advancement of electrochemical energy‐storage devices. Abstract : The micro‐ and nanoscale configurations of the current collectors used in lithium‐ion batteries are analyzed comprehensively and critically. Two new characteristic properties of 3D‐hierarchical current collectors are proposed. The greater the values of the properties, the greater the enhancement of the maximum capacity and capacity retention. The new concepts are beneficial for the design and advancement of future‐generation electrochemical energy‐storage devices.